Hiding in Plain Sight: Κίνησις at the Core of Heidegger’s Work. Prolegomenon - Sheehan, Thomas (Bollettino Filosofico, 2020)
Thesis: The tacit presupposition underlying all of Heidegger’s work, both early (regarding Dasein) and late (regarding Ereignis), was his retrieval of the unsaid in Aristotelian κίνησις. As the prologue to a work-in-progress, this essay discusses how Heidegger’s approach to phenomenology laid the groundwork for his rereading of κίνησις. Heidegger argued that Aristotle (1) understood κίνησις ontologically as a form of being and (2) worked within an implicit proto-phenomenological reduction of being (οὐσία) to intelligibility (παρουσία). Heidegger, in turn, interpreted παρουσία in terms of ἀλήθεια on three distinct but interrelated levels. This prologue prepares the way for a discussion of Heidegger’s readings of Physica III 1-3 and Metaphysica IX and their impact on the topics of Dasein and Ereignis. Keywords: Aristotle, Heidegger, kinesis, Movement, Phenomenology